A qualitative study exploring the influence of clinic funding on the integration of family practice nurses in Newfoundland and Labrador. Issue 4 (14th April 2020) - Mathews, Maria; Ryan, Dana; Buote, Richard; Parsons, Sandra; Lukewich, Julia
Abstract: Aim: This study explores the contributions of family practice nurses in primary care across Newfoundland and Labrador funded by fee‐for‐service and alternate payment plans to examine the influence of funding arrangements on nursing roles/activities. Design: A qualitative descriptive design was employed. Methods: Semi‐structured telephone interviews were conducted between March‐July 2018 with physicians and Registered Nurses working in primary care settings in Newfoundland and Labrador. Interviews were transcribed verbatim, and a content analysis approach was used to identify recurring themes. Results: Clinic funding was instrumental in the integration of family practice nurses into primary care settings and influenced roles/activities. In fee‐for‐service practices, nurses work with physicians and focus on one‐on‐one patient care in office‐based settings, whereas nurses in alternate payment plans practices work more independently, in a wider range of settings and with emphasis on both individual and group‐based encounters. Compared with alternate payment plans practices, fee‐for‐service practices tend to be more restrictive due to physician billing requirements.